The Effect of Compound Exercises For Improving Strength Defined By Speed and the Accuracy of Jump Shot In Yong Handball Players - Mohameed, Alaa (Journal of Physical Education, 2017)
The aim of the research was to identify the effect of compound exercises forimproving strength defined by speed and the accuracy of jump shot in young handballplayers. The researcher hypothesized the positive effect of compound exercises on theimprovement of strength defined by speed and the accuracy of jump shot in handball. Theresults showed that using compound exercises led to the improvement of strength defined byspeed and the accuracy of jump shot in handball. Finally the researcher recommendedconcentrating on compound exercises due to their great effect on developing special physicalabilities and jump shot in handball.